KETERKAITAN KESEHATAN SPIRITUAL (SPIRITUAL WELL-BEING) DAN ORIENTASI KEPUTUSAN ETIS (ETHICAL ORIENTATION OF DECISION MAKING) (Studi Empiris terhadap Para Pembuat Keputusan di Indonesia Tahun 2016) - Ardana, I Cenik; D, Elizabeth Sugiarto; Yuniarwati, Yuniarwati (Jurnal Akuntansi, 2017)
Specifically, the purpose of this study is: (1) to test the validity and reliability of the measurement model of Fisher's spiritual well-being (SWB) construct (2010); (2) to test the validity and reliability of the measurement model of Forsyth’s ethical orientation of decision-making (EDM) construct (1980), and (3) to examine the correlation of Fisher’s SWB variables with Forsyth’s EDM variables (1980). Testing instruments or measurement models uses confirmatory factor analysis and Cronbach Alpha's reliability and testing correlation uses Perlson's correlation. The data is processed with SPSS version 22. The results of this study showed that: (1) the measurment model of Fisher’s SWB construct is valid and reliable; (2) the measurment model of Forsyth’s EDM construct is also valid and reliable. It is also concluded that there is a positive and significant correlation between ideal spiritual well-being (ISWB) construct, either in whole (ISWB) and each dimension (ICSWB, IPSWB, ITSWB, IESWB) with ideal ethical orientation of decision-making (IEDM). There is also a positive and significant relationship between lived spiritual well-being (LSWB) construct as a whole with relative ethical orientation of decision-making (REDM). In testing the correlation of each dimension of LSWB construct (LCSWB, LPSWB, LTSWB, LESWB) with REDM construct, despite all the dimensions of LSWB shows positive correlations with REDM, but the level of significance of the association varies.